It's in the news: Characterising Indonesia's wild bird trade network from media-reported seizure incidents. (March 2020) - Indraswari, Karlina; Friedman, Rachel S.; Noske, Richard; Shepherd, Chris R.; Biggs, Duan; Susilawati, Connie; Wilson, Clevo
Abstract: Devising strategic conservation plans to curb Indonesia's wild bird trade is pivotal to protect species. However, limited understanding of nation-wide trade network patterns could hinder this urgently necessary action. Currently, available information either have restricted geographical scope or is focused on trans-national analysis, limiting understanding of domestic-level nation-wide spatial movement and patterns of traded birds. In this paper, we use media-reported local seizures to understand patterns in a domestic-level wild bird trade network. Indonesia's bird trade network involved 18 countries (including Indonesia), all 34 provinces, and 132, 945 confiscated birds from 157 species. Songbirds (Passeriformes) (83.8% of all birds) dominated the trade, with the highest number of birds in demand for songbird competitions and listed as of conservation concern in the IUCN Red List. The most important region and the main transit point was Jakarta, the most important source of birds was Lampung and the most important destination for birds was West Java. Malaysia was the most important international source of songbirds (mostly smuggled into Indonesia), while the Philippines was the main international destination for the smuggling of Parrots and Cockatoos. Seizures mostly occur near transit and destination regions, and fewer near source regions. Despite the identified patterns, it is likely a small portion of the actual size of Indonesia's bird trade. This paper provided a low-cost approach for a rapid wildlife trade network analysis and could be easily used to identify trade patterns of other taxa in other countries.